Recuperación de cartera vencida y su incidencia en la rentabilidad de la agencia Quevedo banco D-miro del año 2023 - Solórzano Moreira, Jennifer Damaris (2025)
The recovery of non-performing loans directly influences institutional profitability, although it faces significant difficulties due to high delinquency rates, a lack of effective communication, and inefficient credit management. Therefore, this research aimed to evaluate the recovery of non-performing loans and how it impacts the profitability of the Quevedo Agency of Banco D-Miro during 2023. To this end, a survey was conducted with a sample of 228 clients with delinquent loans at this financial institution. In addition, an analysis of the credit records existing at the Quevedo Agency of Banco D-Miro in 2023 was conducted. The results obtained reflected that the main causes of delinquency in the loan portfolio of the Quevedo Agency of Banco D-Miro in 2023 are related to economic factors such as inflation, excessive indebtedness, the national economic situation, and loss of